PERAN INOVASI PEMASARAN DALAM MEMPERTAHANKAN EKSISTENSI TOKO ELEKTRONIK UFO DI PALANGKA RAYA: The Role Of Marketing Innovation In Maintaining The Existence Of UFO Electronics Store In Palangka Raya - Hypranka, April; Tobing, Roynaldo; Sawaludin, Sawaludin; Fajriyah, Selvianur (Ganec Swara, 2025)
This study aims to analyze how marketing innovation plays a role in maintaining the existence of the UFO Electronics Store in Palangka Raya amidst increasingly fierce competition in the electronics business, both offline and online. The research method used is descriptive qualitative with direct interviews with store promoters and direct observation. The results of the study indicate that the UFO Electronics Store's marketing innovation lies not only in digital promotion strategies, but also in improving service quality, strengthening customer relationships, and implementing the 5S service principles (Smile, Greet, Greet, Polite, and Courteous). The combination of excellent service, active digital promotions, and a commitment to customer satisfaction has proven effective in maintaining store loyalty and competitiveness in an ever-changing market